PENGARUH UMUR BIAK DAN POSISI DAUN TERHADAP MORFOGENESIS DARI DAUN KENTANG HITAM (Solenostemon rotundifolius (POIR) JK Morton) IN VITRO - Tatin Suherlina; Aryani Leksonowati; Witjaksono (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2011)
Plant regeneration via somatic embryogenesis or organogenesis is a key for manipulation of somatic cells in vitro. Organogenesis from leaf inoculum, petiole and stem segments of in vitro black potato (Solenostemon rotundifolius (Poir) JK Morton) is influenced by the balance of the concentration of BA and NAA in the culture medium. However, organogenesis could also be affected by factors inherent to the inoculums. This paper reports the influence of leaf position on the in vitro shoots and culture age on the formation and production of shoot adventives from leaf inoculum. Leaves excised from shoots of 3–8 week-old culture and leaf position 1-5 from apical to basal was used as inocula. The highest percentage (83.3%) of adventitious bud develops at cultures age of 5 weeks with the average number of shoots 6.1. The highest percentage of bud development occurs at leaf position number 2-4, with the percentage of buds of 83.3, 76.2 and 76.2, respectively with the average number of shoots of 3.19, 2.10 dan 2.38 respectively. Organogenesis that produces the highest shoot production of 18.6 per Petri dish was obtained from leaves derived from the 2nd leaf from apical of 5 week-old culture inoculated on MS medium enriched with 5 mg/l BA and 0.1 mg/l NAA.